LURC’s Challenge: Managing Growth in Maine’s Unorganized Territories - Bley, Jerry (Maine Policy Review, 2007)
Maine’s Land Use Regulation commission (LURC) oversees an area covering roughly half the state. Plum Creek’s Moosehead Lake Concept Plan has brought LURC into the spotlight. Jerry Bley presents the history of this unique agency, the lands under its jurisdiction, how it has managed development, and what may lie ahead. In developing its Comprehensive Land Use Plan update, LURC needs to seek common ground for solutions that preserve the unique qualities of the area in its jurisdiction, while providing landowners opportunities to realize the financial values of their lands.
Keywords: Maine Land Use Planning Commission; LURC; Maine Unorganized Territories; conservation